Energy insecurity in Turkey: Opportunities for renewable energy - Omid Shokri Kalehsar (Asian Development Bank Institute (ADBI), 2019)
Turkey's energy market has expanded over the course of the past decade at a pace that only the People's Republic of China (PRC) has approached. This shows that Turkey has serious potential. To achieve the energy targets for 2023, there is an expectation that the market must receive investments worth 130 billion. In terms of cooperation with the European Union, renewable energy is a promising route, as both parties face energy challenges due to the limited availability of fossil fuels. Increasing the use of renewable energy in electricity generation can also play a significant role in realizing Turkey's long-term goal of forming a natural gas corridor within its borders. The National Energy and Mining Policy, which the Ministry of Energy and Natural Resources initiated, aims to reduce the dependence on external energy in favor of renewable sources. In the final quarter of 2017, energy generation from water, groundwater, wind, and solar and biological waste reached 32%, exceeding the 2023 target of 30%. When Turkey can create and develop its own renewable sources and overcome the technological and financial challenges, it could enjoy a wealth of diversity, independence, and sustainability in the energy sector. In Turkey, with its young population dynamics, producing energy from renewable sources has much more importance than in other countries. This paper, after revising the global renewable energy supply and demand conditions and the energy strategies of countries like the People's Republic of China and the European Union, will analyze Turkey's strategy for energy generation in detail. The focus will be on how the use of renewable energy will contribute to the energy security and growth of the Turkish economy.
Keywords: F60; N40; N50; 330; renewable energy; energy security; economic development; energy transition